Pseudovascular Squamous Cell Carcinoma of the Oral Cavity: A Diagnostic Pitfall About a Case. Issue 14 (November 2021) - Derqaoui, Sabrine; Elouazzani, Hafsa; Boujida, Ismail; Sayad, Zahra; Zouaidia, Fouad; Cherradi, Nadia
Squamous cell carcinoma is the most common mucosal malignancy of the head and neck. Adenoid pseudo-angiosarcomatous SCC is a rare variant occurring commonly in the skin of the head and neck. However, involvement of oral cavity is extremely rare, with only few case reports in the English literature. Morphologically, the tumor shows marked acantholysis, with anastomozing channels mimicking vascular neoplasms. This variant represents a diagnostic challenge for pathologists, and immunohistochemical analysis remains essential for an accurate diagnosis. Herein, we describe the case of a pseudovascular SCC of the oral cavity in a 67 years old man with a brief revue of the literature to raise awareness on this rare variant; presenting diagnostic difficulties.